SURVEI TINGKAT KEBUGARAN JASMANI PADA SISWA-SISWI TUNA GRAHITA SMP LUAR BIASA NEGERI KOTA SALATIGA (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2012)
AbstrakKondisi tubuh yang bugar sangat penting untuk semua manusia baik namusia normal maupun yang berkebutuhan khusus (cacat tuna grahita). Sample dalam penelitian ini adalah 28 siswa. Instrumen yang digunakan dalam penelitian ini adalah Tes Kesegaran Jasmani Indonesia anak usia SMP umur 13-15 tahun,.Tes yang digunakan untuk mngetahui kebugaran jasmani adalah 1.) Lari 50 meter, 2.) Pull Up, 3.) Sit Up, 4.) Vertikal Jump, 5.) Lari 1000 meter, dan selanjutnya data yang diperoleh dianalisis dengan menggunakan analisis deskriptif persentase. Hasil tes kebugaran jasmani siswa putra tuna grahita terdapat 0% kategori baik sekali, 0% kategori baik, 5 siswa (25%) kategori sedang, 12 siswa (60%) kategori kurang, dan 3 siswa (15%) kategori kurang sekali. Sedangkan untuk kebugaran siswa putri tuna grahita terdapat 0% kategori baik sekali, 0% ketegori baik, 3 siswi (38%) kategori sedang, 5 siswi (63%) kategori kurang, dan 0% kategori kurang sekali. Dari hasil tersebut dapat diketahui kebugaran jasmani siswa-siswi tuna grahita SMP Luar Biasa Negeri Kota Salatiga termasuk dalam kategori kurang.AbstractConditions of a fit body is essential for all good men namusia normal and special needs (handicapped and mentally retarded tuna). The instruments used in this study was Freshness Test Physical Indonesia junior age children ages 13-15 years. Tests used to mngetahui physical fitness is 1.) Run 50 feet, 2.) Pull Up, 3.) Sit Up, 4.) Vertical Jump, 5.) Running 1000 meters, and then the data obtained were analyzed using descriptive analysis percentage. Physical fitness test results of students mentally impaired son are very good 0% category, both categories of 0%, 5 students (25%) were category, 12 students (60%) less category, and 3 students (15%) was less category. As for the fitness of students and mentally retarded daughter tuna category there are very good 0%, 0% good categories, three students (38%) categories were, 5 students (63%) less category, and 0% category is less so. From these results it can be seen physical fitness mentally impaired students Extraordinary State junior Salatiga included in the category of less. Advice can be given is the need to increase physical fitness impaired and mentally retarded students through adaptive physical education interesting and fun as well adapted to the abilities of the students and conducted regularly and continuously.